Investigation on the suitability of natural gas hydrate formation prediction simulation packages and its implementation conditions - Alnaimi F.B.I.; Lim H.C.L.; Sahed A.; Al Salim H.S.; Nasif M.S. (Universiti Putra Malaysia Press, 2023)
In natural gas processing, carbon dioxide is one of the major streams contaminate from the gas reservoir and must be removed, as it reduces the energy content of sales gas. In order to remove huge amounts of carbon dioxide (CO2), gas hydrate is used to capture CO2. However, the high formation of hydrate will inhibit clogs in gas pipelines. Hence, this research presents literature on hydrate formation, prediction of methane-carbon dioxide (CH4-CO2) gas mixture, by using simulation packages of Aspen Hysys 7.2, K-factor, VMG SIM Ver. 6 and BR & E ProMax 2.0. Peng-Robinson model was used in all simulation packages. Simulation results obtained were then compared with experimental data from previous literature sources. The simulation results showed that the higher the concentration of CO2 in CH4-CO2 gas mixture, the lower the pressure required for CO2 hydrate to form throughout the predicted temperature range from-20C to 20C. Universiti Putra Malaysia Press.